Optimasi Parameter Proses Injection Molding Terhadap Inner Snap Diameter dan Netto Produk Pot Cream 10 Gram Metode Response Surface - Dharu Fadillansyah Putra; Pranowo Sidi; Nurvita Arumsari (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
Along with the times and advances in science and technology, plastics are increasingly being used by people in various products because of their diverse interests. Many industries make plastic as the main raw material in the production process. Processing of plastic seeds until it became finished products can be done in many ways one of them is injection molding. But there are some obstacles when plastic products are made in large quantities, so they need to improve the quality of products they are produced.One way to improve the quality of products is by optimizing the parameters. Parameter optimization is a technique used in the manufacturing process to produce the best product. This study aims to optimize injection molding parameters such as injection time, injection pressure and holding time to optimize inner snap diameter and netto on pot cream products. Each parameter has 3 levels which are designed using Box-Behnken method. In this research using ANOVA method to analyze experimental data and the optimization of inner snap diameter and netto in injection molding process is done by using response surface method.Based on the results, it is known that the parameters of injection time, and holding time has an influence on the inner snap diameter. While for the netto all parameters have influence such as injection time, injection pressure, and holding time. For optimization, the configuration of injection time parameter is 3.74 seconds, injection pressure is 47%, and holding time is 1.5 seconds which produce 46.11 mm of inner snap diameter and netto 8.7 gram.